Extraction of high-added-value compounds from codfish (Gadus morhua L.) salting wastewater - Ferraro, Vincenza; Braga da Cruz, Isabel; Ferreira Jorge, Ruben; Pintado, Manuela E. (HAL CCSD, 2013)
The fish processing industry is widespread and extremely varied in terms of type and scale of operation. Codfish (Gadus morhua L.) is one of the most processed white fish in Europe, where it is usually consumed salt‐cured. Significant amounts of waste and byproducts result from its processing. Salt induces the release of substantial volumes of physiological water (∼200 l for each ton of fresh fish), which drains away significant amounts of nutrients (∼10 g/l). In this chapter we discuss the recovery of muscle proteins and free amino acids from codfish salting wastewater by sorption using a commercial resin. The free amino acid extract shows important biological properties, such as antioxidant activity and in vitro intestinal permeability. The chapter discusses the application of this mixture and of muscle protein in food, feed, cosmetic, and pharmaceutical formulations.